Taaruf Online dan Offline - Hildawati Hildawati; Ayu Lestari (Emik, 2019)
Taaruf is a way of introducing men and women who wish to get married based on Islamic law. The essence of taaruf is lack of interaction between potential partners so that they commonly mediated by a go-in-between. In the past, the go-in-between was someone who knew personally the two potential partners, but now taaruf can also be mediated by social media. This study deals with taaruf taaruf online through Instagram and Whatsapp and compares it with offline taaruf, which is carried out without involving social media provider. We combine between observation and interview as our data collection methods. Observation was conducted on taaruf account in social media Instagram and Whatsapp by examining uploaded images or video and their captions. Interview was conducted into two: direct interview and chatting through social media Instagram and Whatsapp or direct call in order to explore the process of online taaruf and offline taaruf, the involvement of the admin as the go-in-between, how is the involvement of the intermediary in offline taaruf, and the motivation of the people who get involved in taaruf processes. The results show that taaruf was conducted through a go-in-between that facilitates interaction between potential partners who have the intention to get married. While in the past, taaruf was carried out without any contribution to social media, the initial introduction was started from the closest people around the potential candidate who wanted to get married, such as a teacher who asked for religious knowledge, religious teacher or religious teachers’, friend and family. In this digital era, taaruf can also be done through social media, by using taaruf accounts on Instagram. Since the introduction of taaruf through social media, the term used for the type of first taaruf adapted to the second type of taaruf, namely taaruf online and taaruf offline. Although each type has different method at several stages, both can run successfully until they get marriage, each has advantages and disadvantages. Online taaruf gives participants many options, unfortunately their biodata is potentially misuse by others. Whereas in offline taaruf, the biodata of participants is relatively safer and more valid because the go-in-between knows them personally. However, the participants have no option other than the one who is provided by the go-in-between.